STRATEGI GURU DALAM MENINGKATAKAN MINAT ANAK BEKEBUTUHAN KHUSUS TUNAGRAHITA DALAM MENGIKUTI PEMBELAJARAN PENJASORKES DI SEKOLAH LUAR BIASA NEGERI OELAMASI KABUPATEN KUPANGTAHUN AJARAN 2019/2020 - Rame, Simon Petrus; Blegur, Yusuf; Selan, Melvianus (Jurnal Ilmu Pendidikan Jasmani Kesehatan Dan Olahraga, 2021)
This study aims to determine the teacher's strategy in increasing the interest of children with special needs at the time of starting and closing learning, in physical education learning process activities in schools towards teacher strategies in the physical education teaching and learning process at SLB N Oelamasi, Kupang Regency. This research method uses qualitative research. Based on the findings in the study which showed that the two teachers were able to mentally prepare students to take part in learning by providing motivational enthusiasm before entering core learning, providing interesting motivation so that students were encouraged to take part in learning by providing profiles / sports figures they liked so that they were encouraged to participate in learning activities. learn with enthusiasm, provide a clear picture of the goals and limits of learning so that students know the goals and limits of learning and make students aware of the relationship between experiences that are already known in the environment and the learning to be studied. Evaluate and review the mistakes made by students in carrying out movements/activities in the learning process to strengthen student understanding and provide follow-up actions to develop knowledge/ability by giving homework or assignments.